Whole mitochondrial genome analyses of Han population from Shandong of China using massively parallel sequencing - Zhang, Jiashuo; Li, XueBo; Chen, Anqi; Ding, Mingxia; Li, Liangliang; Qi, Yinghua; Ding, Chunli; Cai, Dawei; Zhang, Suhua (Frontiers in Genetics, 2024)
IntroductionMitochondrial DNA (mtDNA) has been extensively utilized in archeology, human evolutionary genetics, and forensic genetic for over three decades, primarily due to its maternal inheritance and relatively high mutation rate. The Chinese Han, the largest and most widely distributed ethnic group in China, have been the focus of numerous genetic studies. However, the forensic parameters and genetic structure of the Shandong Han, specifically in relation to the whole mitochondrial genome, remain undocumented.MethodsWe performed whole mitochondrial genome sequencing on 141 unrelated Han individuals from Shandong province using massively parallel sequencing.ResultsA total of 135 unique mtDNA haplotypes were identified, classified into 105 haplogroups, resulting in a haplotype diversity value of 0.9993. The discriminatory capacity of whole mitochondrial genome was calculated at 0.9574, compared to 0.8936 when only the control region was analyzed. The majority of the haplogroups observed were specific to East Asian lineages, including D4, D5 and F1. Population comparisons revealed that the modern Shandong Han share genetic connections with ancient populations from the Yellow River and West Liao River basins. Additionally, the Shandong Han may have integrated a significant number of maternal lineages from other regions during their development. The demographic expansion of the Shandong Han is estimated to have occurred approximately 9,000 years ago, corresponding to the Neolithic period, a time of significant cultural and technological development.DiscussionThe dataset generated in this study is available in the EMPOP database under the accession number EMP00886 and will serve as an important mtDNA reference for forensic casework in China. The study of whole mitochondrial genome based on the analysis of matrilineal genetic structure of the Shandong Han population can help to enrich the forensic mtDNA reference database in East Asia and provide reference for future archeology and forensic genetics research.